PDA‐Engineered 3D‐Printed Polymer–ZrO 2 Hybrid Scaffolds Enabling Enhanced Radiopacity, Photothermal Therapy, and Cell Migration Modulation - Sumin Kang; Yun‐Jin Jeong; Seokjae Kim; Van Du Nguyen; Songah Jeong; Juyeong Jo; Arunkumar Shanmugasundaram; Jin Uk Jeong; Dong‐Weon Lee; Eunpyo Choi; Hyungwoo Kim (Small, 2026)
ABSTRACT The clinical translation of bioresorbable polymer scaffold is limited by radiolucency, insufficient mechanical strength, and the absence of post‐implantation therapeutic control. This study introduces a multifunctional scaffold that addresses these challenges through a polymer–ceramic nanocomposite architecture and bioinspired surface modification. ZrO 2 nanoparticles are uniformly embedded into poly(ε‐caprolactone) (PCL) via solution blending and fabricated into vascular scaffold by fused deposition modeling, yielding improved elastic modulus and radial strength while preserving elastic recovery. The ceramic phase provides intrinsic and sustained x‐ray visibility in vitro, in vivo, and during 100‐day perfusion, outperforming conventional contrast‐agent‐based strategies. A subsequent polydopamine (PDA) coating step enables efficient near‐infrared (808 nm) photothermal functionality, which was leveraged for photothermal therapeutic modulation and repeatable, pulse‐controlled release of paclitaxel. Cellular evaluation of vascular smooth muscle cell viability and migration underscores the therapeutic relevance of this externally triggered strategy for restenosis prevention. Overall, by integrating mechanical reinforcement, x‐ray imaging capability, and remote therapeutic activation within a single PCL‐based hybrid platform, this system addresses the long‐standing clinical limitations of polymeric vascular scaffolds and offers a promising strategy for next‐generation theranostic vascular implants.